New mixed alkali effect in the ac conductivity of ion-conducting glasses - Cramer, Cornelia; Brunklaus, Sabine; Gao, Young (Physical review letters)
We have determined the first wide-range conductivity spectra of a mixed alkali glass system, extending from 10−3  Hz to 1.3 THz. We report on a new mixed alkali effect in the ac conductivity that is evident even if the low-frequency contributions (linked to hopping motions of the mobile cations) are removed from the experimental spectra. From our results we conclude that the nonhopping contributions to the ac conductivity involve both the mobile ions and the glassy network.